The Effect of Organizational Communication on Employee Work Motivation in the State-Owned Sector - Fazli, Luthfi; Akbar, Muhammad Fikri; Allifiansyah, Sandy (Journal of Digital Marketing and Communication, 2025)
The PT Bank Negara Indonesia (Persero) Tbk Kaliabang Branch Office, often known as the BNI Kaliabang Branch Office, is a state-owned corporation that provides a variety of financial services to promote Indonesia’s economic growth and industrial development. The purpose of this study was to examine the relationship between organizational communication and employee motivation at the BNI Kaliabang Branch Office and to investigate how communication influenced motivation. The study adopted a quantitative descriptive method with a total sample of 80 respondents. To assess the causal relationship, data were analyzed using descriptive statistics and basic linear regression. The results showed that organizational communication had a significant impact on employee motivation, as demonstrated by a determination coefficient of 57.6% and a significance level of 0.000. The study highlighted that organizational communication within the branch was effective, and employee motivation levels were high. Despite these positive findings, areas for improvement were identified, including leveraging electronic media to enhance message dissemination, fostering employee skills to boost creativity and productivity, and introducing a “Best Employee of the Month” program to further motivate staff. These recommendations aimed to strengthen the organization’s communication strategies and sustain high employee performance, ultimately contributing to its overall operational success.